GRAMMATICAL ERRORS MADE BY THE TENTH GRADE STUDENTS OF SMK GRAFIKA BINA MEDIA MEDAN IN WRITING ADVERTISEMENT TEXT - Samosir, Angeline Elisabeth; Lumban Raja, Viator; Ginting, Fiber Yun A (Kairos English Language Teaching Journal, 2021)
This research is an attempt to find out the types of errors made by the tenth grade students of SMK Grafika Bina Media Medan based on linguistic category, morphology and syntax and the dominant errors in each category. The population of this research is the tenth grade students amounting 56 students of three classes. As many as 30 students are taken as a sample which is randomly taken 10 students from each class. The research employed the descriptive qualitative research analysis. Based on the result of the analysis, there are 117 errors found in the students’ writing advertisement text. In the morphological area, there are errors in article, possessive case, third person singular and comparative so there are 35,90% errors. Meanwhile, in syntax area the writer found noun phrase, verb phrase, noun and verb construction, word order and some transformation, there are 64,10%. in conclusion, the dominant errors made by the tenth grade students of SMK Grafika Bina Media Medan is syntax errors namedly noun phrase.